The UK Teaching Excellence Framework (TEF) as an illustration of Baudrillard's hyperreality. Issue 3 (4th May 2019) - Canning, John
ABSTRACT: This article examines the 'Teaching Excellence Framework' (TEF) for UK universities through the lens of Jean Baudrillard's concept of hyperreality. I argue that the TEF is a hyperreal simulacrum, a sign which has no traceable genealogy to the practice of learning and teaching.